A needs-based analysis of teaching on vaccinations and COVID-19 in German medical schools - Baessler, Franziska; Zafar, Ali; Mengler, Katharina; Natus, Ricarda Nadine; Dutt, Anne J.; Kuhlmann, Manuel; Çinkaya, Emre; Hennes, Simon (Vaccines, 2022)
The COVID-19 pandemic highlights the need for improving public confidence in vaccines. Academic gaps and redundancies on vaccinations must be identified to revise the medical curriculum for up-to-date training of medical students. This cross-sectional survey assessed the status of vaccine-related teaching in general and specific to COVID-19 in medical schools across Germany. A total of 4313 medical students completed a questionnaire comprising items on national learning goals and perceived needs for teaching on vaccinations. Mixed methods were used to analyse data quantitatively for relative frequencies (%) and correlations between teaching items and semesters (Spearman’s rho), and qualitatively (content analysis). Our findings showed that 38.92% of the students were dissatisfied with teaching on vaccine-preventable diseases, but the perceived satisfaction increased in later semesters (r = 0.46, p < 0.001). Moreover, 75.84% and 68.15% of the students were dissatisfied with teaching related to vaccine scepticism and vaccine-related communication strategies, respectively. Furthermore, 63.79% reported dissatisfaction with teaching on COVID-19 disease and 72.93% with teaching on COVID-19 vaccines. A total of 79.12% stated they educated others on COVID-19 and its vaccines and 75.14% felt responsible to do so. A majority of the medical students were dissatisfied with teaching on dealing with vaccine scepticism, communication strategies and COVID-19 vaccines. We recommend practice-oriented vaccine education, especially for teaching communication skills to medical students.
Gesehen am 18.08.2022